(untitled) (Swiss Medical Weekly, 2018)
Combined antiretroviral treatment (cART) has reduced mother-to-child transmission (MTCT) of the human immunodeficiency virus (HIV) to virtually zero in industrialised countries, where strictly bottle feeding is recommended for HIV-infected mothers, and to as low as 0.7% after 12 months in low-resource settings, where breastfeeding is strongly encouraged. Given the theoretically very low risk of transmission by breastfeeding with cART, and the advantages and benefits of breastfeeding, also in industrialised countries, the strong recommendation to HIV-infected mothers to refrain from breastfeeding in this setting may no longer be justified. We have evaluated risks of breastfeeding for HIV MTCT in the light of accessible cART, the general benefits of breastfeeding, and the women’s autonomy to consent to any intervention. As we found no evidence in the literature of HIV MTCT via breastfeeding whilst on effective cART, we identified a situation of clinical equipoise. We propose how to proceed in Switzerland when HIV-infected women consider breastfeeding. We advocate a shared decision-making process and suggest a list of topics on which to provide unbiased information for the HIV-infected mother to enable her comprehensive understanding of one or the other decision. Although breastfeeding still should not be actively recommended in Switzerland, any HIV-infected mother, regardless of her geographical and cultural background, who decides to breastfeed should be supported by the best strategy to achieve optimal medical care for both herself and her child. This includes continuous support of cART adherence and regular maternal HIV plasma viral load monitoring.